Estigmas sociais e homofobia normativa: Uma análise da discriminação acerca do sangue gay - CUNHA, Raí Leorne Castro (2022)
The objective of this work is to analyze the evolution of LGBTQIA + community's rights, the social stigmas suffered by gay men and the normative homophobia embodied in the gay men's temporary inaptitude in blood donation current in the RDC n. 34/2014 regulations of ANVISA and Ordinance No. 158/2016 of the Ministry of Health. For that matter, the evolutionary history of AIDS in Brazil and in the world was approached as a way of understanding the creation of safety measures which have made a certain group of people with sexual risky behavior unfit for blood transfusion, intending to prevent contamination of receivers. In this work, several bibliographies and normatives were also analyzed, so that the research demonstrated that despite the past of world history that has condemned, for a long time, the gay community to be stigmatized for having risky sex, this stigma must be surpassed, given that this community has been undergone several rights restrictions throughout history which have demonstrated that the fundamental rights of the LGBTQIA + community must be guaranteed not only through the CFRB / 1988 but also by means of international treaties signed by Brazil. From the analyzed normatives it was noticed the contrariety in the requirements to make this blood donor unfit for donation; therefore it was realized that the normatives are prejudiced and unconstitutional texts, which try to perpetuate the stigmas suffered by gay men in a way that violate the right to equality and non-discrimination of gay men.